1997
DOI: 10.1046/j.1365-2265.1997.1911029.x
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly, colonic polyps and carcinoma

Abstract: Patients with acromegaly have an increased risk of developing colorectal cancer and a significantly higher prevalence of tubulovillous adenomas compared with normal subjects. Routine surveillance colonoscopy is indicated in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
2
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(156 citation statements)
references
References 21 publications
3
145
2
6
Order By: Relevance
“…Several previous studies have suggested that these patients are also at an increased risk of neoplasia, especially colorectal cancer and pre-malignant adenomatous polyps, although the degree of risk remains under debate (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In our original series, we observed 5% to have a carcinoma and 25% to have one or more adenomas (11). Similar findings have been reported by other groups (12).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Several previous studies have suggested that these patients are also at an increased risk of neoplasia, especially colorectal cancer and pre-malignant adenomatous polyps, although the degree of risk remains under debate (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In our original series, we observed 5% to have a carcinoma and 25% to have one or more adenomas (11). Similar findings have been reported by other groups (12).…”
Section: Introductionsupporting
confidence: 78%
“…The advantage of the present study is that it reflects the experience of a single large cohort of patients from a single institution, and all the colonoscopies, except two, were performed by the same skilled operator, who visualised the entire colon in 99% of procedures. For less experienced operators, the success rate is only 70% (11).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the variation of polyps and cancer prevalence at this site (9-38%) in different series (12)(13)(14)(15)(16), the correlation between acromegaly and tumors is frequently observed, and many studies have shown that an increase in IGF-I is correlated with an increase in the prevalence of polyps (12,13), adenomas (17) and proliferation of colon epithelium cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Patients with acromegaly, a disease characterized by abnormally high levels of GH secretion, are at an elevated risk for colorectal cancer. [7][8][9] GH is the main determinant of circulating levels of IGF-I and its main binding protein, IGFBP-3. 1 The GH1 gene is polymorphic and a substitution polymorphism (T1663A) is considered to be associated with GH production.…”
Section: Introductionmentioning
confidence: 99%